The relationship between helium-rich gas and regional shale in the Sichuan Basin, Southwest China - He, Jianglin; Li, Shuangjian; Zhao, Ankun; Wang, Dong; Gao, Jian; Zhou, Xiaolin; Ahmed, Mohamed S.; Wang, Zhenghe; Zhu, Lixia (Frontiers in Earth Science, 2024)
Despite over 60 years of helium development in the Sichuan Basin, the mechanism of helium enrichment remains poorly understood. Helium-rich gas is primarily found as gas composition analysis in the fields. This study explores the relationship between helium distribution and two regional shale formations (the Qiongzhusi and Wufeng-Longmaxi formation), basing on the spatial distribution of these shales, structural profiles, and reported helium concentrations. Our findings indicate a typical trend of helium enrichment within the Sichuan Basin, where helium concentrations generally increase from the basin margins toward its center. The R/Ra ratios in the natural gas are consistently below 0.1, indicating that the helium mainly originates from the granite basement. The Wufeng-Longmaxi Formation is absent from central to western parts of this basin. The hydrocarbon generation intensity of this shale is 3,627.26 m³/m2, which is 25,896.7 times greater than its helium generation intensity (0.14 m³/m2). Its helium capture time is short (237 Ma). There is no obvious correlation between the distribution of helium concentration and Wufeng-Longmaxi shale. The Qiongzhusi shale extends across the entire Sichuan Basin. Its hydrocarbon generation intensity is approximately 57 m³/m2, which is 267.4 times greater than its helium generation intensity (0.27 m³/m2). Beneath this shale, the Pre-Sinian granite exhibits a helium generation intensity exceeding 0.51 m³/m2, acting as the primary helium source rock in the basin. The helium capture time of Qiongzhusi shale is 435 Ma. Helium concentration increases as the burial depth of the Qiongzhusi shale decreases, and helium becomes isotopically lighter in the direction of fluid potential drop. This indicates that helium enrichment in the Sichuan Basin is predominantly influenced by the Qiongzhusi shale. From maximum burial depth to present, helium solubility in water has decreased by approximately 63.6% and 54.3% in the Wufeng-Longmaxi and Qiongzhusi shale respectively, suggesting that uplift processes contributed to helium degassing into gas reservoirs. The regional shale influenced the long-distance migration of helium, although faults can alter this pathway. Faults may either promote helium accumulation in shallow gas fields, such as the Jinqiu gas field, or lead to helium loss, as observed in the southeastern region of the Sichuan Basin.